Ecosystem of VAT Administration in E-Commerce: Case of the Eastern Europe Countries. - Abramova, A. S.; Zhavoronok, A.V.; Shaposhnykov, K.; Liutikov, P.; Skvirskyi, I.; Lukashev, O. (Estudios de economía aplicada, 2021)
Within the article, a bibliographic analysis of e-commerce research is provided. In particular, using the Scopus database it was established that research of this type of commerce began in 1996 with gradual emergence of services for the sale and purchase of goods and services online. In addition, retrospective analysis of scientific publications in this field allowed to establish the wave of scientists’ interest in conducting e-commerce research due to the level of the information technology development, which directly determines the e-commerce development in the world. In addition, within the article, scientific fields in which the majority of scientific works have been prepared for its study are analyzed, and the countries in which the most research is conducted are considered/
Keywords: e-commerce; commerce, e-business; bibliographic analysis; digital technologies; digital economy